Direct Oral Anticoagulants for the Prevention and Acute Treatment of Cancer-Associated Thrombosis - Attard LM; Gatt A; Bertoletti L; Delluc A; Riva N (Vascular Health and Risk Management, 2022)
Laura M Attard,1 Alex Gatt,2 Laurent Bertoletti,3– 5 Aurelien Delluc,6 Nicoletta Riva2 1Medical School, University of Malta, Msida, Malta; 2Department of Pathology, Faculty of Medicine and Surgery, University of Malta, Msida, Malta; 3Service de Médecine Vasculaire et Thérapeutique, CHU de St-Etienne, Saint-Etienne, France; 4INSERM, UMR1059, Université Jean-Monnet, Saint-Etienne, France; 5INNOVTE, CHU de Saint-Etienne, Saint-Etienne, France; 6Ottawa Hospital Research Institute, Department of Medicine, University of Ottawa, Ottawa, ON, CanadaCorrespondence: Nicoletta Riva, Department of Pathology, Faculty of Medicine and Surgery, University of Malta, Msida, MSD 2080, Malta, Email nicoletta.riva@um.edu.mtAbstract: Cancer is a major risk factor for venous thromboembolism (VTE), and cancer-associated thrombosis (CAT) constitutes approximately 15– 25% of all VTE cases. For decades, the standard treatment for CAT used to be daily subcutaneous low molecular weight heparin (LMWH). Data on the safety and efficacy of the direct oral anticoagulants (DOACs) in this population emerged only in recent years and specific DOACs were included into recent guidelines recommendations. In this narrative review of the literature, we reported the results of the phase III randomized controlled trials that evaluated the DOACs for the prevention and the acute treatment of CAT. For the acute phase treatment, the anti-Xa inhibitors (apixaban, edoxaban, rivaroxaban) showed better efficacy than LMWH in preventing VTE recurrence; however, rivaroxaban and edoxaban were also associated with an increased risk of bleeding events. For primary prevention of CAT in ambulatory cancer patients starting chemotherapy, apixaban and rivaroxaban showed better efficacy than placebo but a trend towards higher bleeding rates. Recent guidelines suggest the DOACs for the treatment of CAT in selected cancer patients (eg, low bleeding risk, no luminal gastrointestinal or genitourinary malignancies, no interfering medications). The DOACs are also suggested for primary thromboprophylaxis in selected ambulatory cancer patients at high risk of VTE (eg, Khorana score ≥ 2 prior to starting new chemotherapy, low bleeding risk, no interfering medications).Keywords: cancer, venous thromboembolism, apixaban, edoxaban, rivaroxaban